Social Determinants of Antenatal Care Service Use in Ethiopia: Changes Over a 15-Year Span - Ousman, Seman Kedir; Mdala, Ibrahimu; Thorsen, Viva Combs; Sundby, Johanne; Magnus, Jeanette H. (Frontiers in Public Health, 2019)
Background: Improving maternal health in Ethiopia is a major public health challenge. International studies indicate that it is possible to improve maternal health outcomes through action on the Social Determinants of Health (SDH). This study aimed to explore the SDH that influence the antenatal care (ANC) utilization in Ethiopia over time. Methods: The study used data from the nation-wide surveys conducted by the Ethiopian Central Statistical Agency (CSA) and ORC Macro International, USA in 2005, 2011 and 2016. A negative binomial with random effects at cluster level was used to model the number of ANC visits whereas a multilevel binary logistic regression modelled binary responses relating to whether a woman had at least 4 ANC visits or not. The model estimates were obtained with the statistical software Stata SE 15 using the restricted maximum likelihood method. Results: Although the median number of ANC visits significantly increased between 2005 and 2016, the majority of the women do not obtain the four ANC visits during pregnancy as recommended. The odds of having at least four ANC visits were significantly lower among women: below 20 years, those living in the rural areas, having higher birth order or Muslim. In contrast, higher educational attainment, higher socio-economic status, exposure to mass media and self-reporting decision empowerment were significantly associated with having at least four ANC visits. Conclusion: The use of ANC visits is driven mostly by the social determinants of health rather than individual health risk. The importance of the various SDHs needs to be recognized by Ministry of Health policy and program managers as a key driving force behind the country’s challenges with reaching targets in the health agenda related to maternal health, particularly related to the recommended number of ANC visits.